Strategi Kewirausahaan Dalam Mengembangkan UMKMdi Era Digital - Doni Pratama Putra; Nashihuddin Sahil Alfikri; Yulia Novita; Zetri Rahmat (MUARA EKONOMI : Jurnal Ilmiah Ilmu Ekonomi, Manajemen & Bisnis, 2025)
This research paper discusses the entrepreneurial strategies needed to develop Micro, Small, and Medium Enterprises (MSMEs) in the digital era. The development of digital technology has changed consumer behavior, competition patterns, and business operational models. Therefore, MSMEs are required to adapt through innovation, digital marketing, and the utilization of online platforms. The objectives of this study are to analyze the effectiveness of digital entrepreneurial strategies, identify the challenges faced by MSME actors, and formulate strategic recommendations to enhance competitiveness. This research uses a qualitative descriptive method based on literature review and observation of MSMEs that have implemented digital strategies. The results indicate that digital literacy, social media optimization, product innovation, and customer relationship management are key factors in the success of business development. In conclusion, MSMEs that adopt digital entrepreneurial strategies tend to experience increased market reach, operational efficiency, and strengthening of brand position